ENGLISH-RIGHT TO ABORTION TO RAPE VICTIMS: A SURVEY RESEARCH - Qurratulain Munir Minhas (دی اسکالر, 2022)
In Pakistan, sexual violence against women is the most prevalent type of violence. Rape and other forms of sexual assault are rising rapidly on a global scale. Sexually transmitted diseases, unwanted pregnancies, and the physical effects of rape-injury all result in psychological problems that are frequently disregarded. Women who have been raped are more likely to have sadness, anxiety, and substance abuse, among other mental health issues. As rape instances rise daily, it is necessary to address related issues so that legislation may be properly drafted and put into place to address the problem. Abortion is a contentious issue everywhere, and Pakistan is no exception. Even when a pregnancy results from rape, most conditions do not give a woman the chance to decide for herself. The female is either compelled to bear a child and risk exile, or she commits herself out of fear of oppression and disgrace. It is upsetting that rape victims who become pregnant receive no assistance from Pakistan's legal system. The general belief is that rape victims should have a choice of an abortion because the pregnancy serves as a physical reminder of what she endured. The pro-abortion community views pregnancy as the result of rape, an injury to women, and abortion as a way to help heal that injury. Therefore, a survey will be undertaken in this work to identify and examine the issues that rape victims face in society. The opinions of the medical officials (doctors) and legal counsel will be gathered for this purpose. The survey's results will be compiled in the conclusion at the end.